2009
DOI: 10.1177/0269216309105893
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the implementation of a programme to improve end-of-life care in nursing homes

Abstract: The Gold Standards Framework in Care Homes programme aims to improve the quality of end-of-life care for residents. The impact of introducing phase 2 of the programme to homes in England was evaluated. A pre-post survey design was adopted, focusing on indicators identified as markers of good end-of-life care. The 95 homes in phase 2 of the programme were invited to participate in the evaluation. Homes completed a baseline survey of care provision and an audit of the five most recent resident deaths. The survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 12 publications
1
73
0
Order By: Relevance
“…In three of these studies (50%), 23,31,36 patients in the intervention groups were more likely to die at home. Four studies reported enrollment in hospice, use of hospice services or placing patients on a comfort care plan (two were RCTs).…”
Section: Other Outcomesmentioning
confidence: 99%
“…In three of these studies (50%), 23,31,36 patients in the intervention groups were more likely to die at home. Four studies reported enrollment in hospice, use of hospice services or placing patients on a comfort care plan (two were RCTs).…”
Section: Other Outcomesmentioning
confidence: 99%
“…75 More universal use of advance care directives and palliative care programs should be mandated in RCFs as these reduce hospitalisation rates involving RCF patients by up to 40%. [76][77][78] Even in the absence of advance care directives, simply raising family awareness of the futility of 'heroic' interventions in RCF. Patients with advanced or endstage disease could help substantially reduce unnecessary hospitalisations in this group.…”
Section: Enhancing Acute and Palliative Care In Residential Care Facimentioning
confidence: 99%
“…Yet, there exists a culture of silence surrounding dying that creates a barrier to end-of-life communications in LTC [2,10]. Lack of discussion with the resident and the resident's substitute decision-maker, most commonly a family member, about end-of-life wishes can lead to unnecessary and unwanted medical treatments [11,12], unnecessary transfers to the acute hospital [13], and discomfort and anxiety for both the resident and family [14]. Implementing effective advance care planning (ACP) can improve patient and family satisfaction with care and increase the likelihood that people will die in their setting of choice [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…ACP is viewed as an essential component of a quality palliative care program and provides LTC residents important decision-making opportunities [18][19][20] that can guide their caregivers when they cannot speak for themselves [21][22][23]. Knowing individuals' preferences for care and enabling them to die where they choose are recognized as the gold standard in palliative care [11]. Having comprehensive up to date advance care plans can help staff create a peaceful environment for dying residents and their families within LTC [24] and avoid unnecessary health care expenditures [14].…”
Section: Introductionmentioning
confidence: 99%